Implementation of EU standards on access to justice for vulnerable victims and witnesses: challenges and prospects for Ukraine - Bondarenko, Y. (Аналітично-порівняльне правознавство, 2025)
This article offers a comprehensive analysis of the implementation of European Union standards on access to justice for vulnerable victims and witnesses in the context of Ukraine’s European integration. The topic is highly relevant given the ongoing war and the growing number of individuals requiring legal, psychological and social protection, as well as Ukraine’s commitment to its international human rights obligations. The theoretical and regulatory framework of the study is the EU Directive 2012/29/EU (Victims’ Rights Directive), which establishes minimum standards on the rights, support and protection of victims of crime. Particular attention is paid to its key provisions – such as the right to accessible information, participation in criminal proceedings, special protection measures and compensation. The methodological basis of the study combines a systematic analysis of Ukrainian legislation and policies on victim protection with an examination of international reports and recommendations. Practical examples of implementing human-centred services are considered, such as the establishment of child-friendly and “green” rooms in courts, the introduction of volunteer services, and the development of specialised programs under the “Model Courts” Initiative. The paper examines the activities of the Coordination Centre for Victims and Witnesses Support at the Office of the Prosecutor General of Ukraine, the first institutional mechanism in the country providing comprehensive legal, psychological and social assistance to victims and witnesses, developed with international technical support. The study reviews up-to-date reports from the EU, the Fundamental Rights Agency (FRA), the Council of Europe and the UN Human Rights Monitoring Mission in Ukraine (2023–2025). Findings indicate that despite Ukraine’s political will and the adoption of the “Rule of Law Roadmap,” implementation of Directive 2012/29/EU remains partial. Persistent gaps include the absence of a systematic assessment of victim vulnerability, a lack of mechanisms to prevent repeat victimisation, insufficient obligations to provide timely information on case progress, and limited special support measures during first contact with competent authorities. The article references FRA recommendations (Fundamental Rights Report 2025) calling for the development of a sustainable network of victim support services and translation/ interpretation assistance, improved communication strategies, and the introduction of a unified data collection and monitoring system. The results show that the development of institutional infrastructure, along with the adoption of comprehensive legislation on victims’ rights, are key prerequisites for the successful implementation of EU standards. Systematic training of police officers, prosecutors, judges and defence lawyers on preventing re-victimisation, providing psychological support and ensuring access to legal aid builds the foundation for long-term public trust in justice. The article underscores that harmonising Ukrainian legislation with Directive 2012/29/EU requires not only formal legal alignment but also effective interagency coordination, adequate funding and the development of victim support infrastructure.